Support Group Therapy untuk Menurunkan Kecemasan pada Care Giver Odgj di Desa Srigading - Wiwik Lestari; Triantoro Safaria (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
The purpose of this study group was to see the effect of group therapy in reducing cholesterol in ODGJ care givers. There were 6 participants in the group therapy which was a recommendation from the soul cadres of Srigading village. This therapy is carried out in a form analysis using a combination of qualitative and quantitative methods, with a psychodynamic-oriented approach. Group participants are drawn based on the same problem, namely the conclusion. In carrying out the obligations of the ODGJ giver, he is also a direct member of the family who also feels and feels uncomfortable while accompanying ODGJ. The results show that seen from statistical data there is a decrease in the level of attention of the giver after being given group therapy support. The results of the qualitative data also showed a decrease which was known through individual interviews after being given group therapy support